2020
DOI: 10.1177/1120672120982899
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal choroidal thickness and peripapillary retinal nerve fiber layer thickness in young obese males

Abstract: Objective: Regarding the effect of obesity on subfoveal choroidal thickness (CT) and peripapillary retinal nerve fiber layer (RNFL) thickness, controversial results have been reported in different patient groups. This study aimed to evaluate the effect of obesity on these parameters among young male subjects in comparison with age-matched non-obese healthy males. Methods: This prospective, cross-sectional study included both eyes of 50 obese young males and 50 healthy non-obese young males. The obese and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(56 reference statements)
0
11
1
Order By: Relevance
“…Five of the corresponding authors replied to our emails, 4 of them about association between BMI and OCT measurements and 1 on the unavailability of full-text. Finally, only 1 responded positively, (Uslu Dugan et al) and provided us with the full-text of their study [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the corresponding authors replied to our emails, 4 of them about association between BMI and OCT measurements and 1 on the unavailability of full-text. Finally, only 1 responded positively, (Uslu Dugan et al) and provided us with the full-text of their study [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 included studies in this meta-analysis, 5 measured macular thickness [ 9 , 20 , 26 28 ], 3 measured GC-IPL layer thickness [ 10 , 29 , 30 ], 5 measured RNFL thickness [ 12 , 27 , 28 , 31 , 32 ], and 7 studies measured peripapillary RNFL thickness [ 10 , 11 , 13 , 25 , 26 , 29 , 30 ], 5 measured cup to disc ratio [ 26 28 , 30 , 31 ], and 12 measured choroidal thickness [ 9 , 14 , 20 , 25 28 , 32 36 ]. All the studies reported their data as mean (SD), except one that reported some of the measurements in median (min-max) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graham et al reported significant thinning affecting the T quadrant in the non-ON eyes and also demonstrated that the T quadrant is a very specific marker for detecting changes over time ( 6 ). In another study on healthy young obese males, Dogan et al demonstrated a negative association between BMI and T quadrant pRNFL thickness ( 33 ). Our findings support previous observations that the T quadrant is affected more than other pRNFL quadrants in our cohort of RRMS.…”
Section: Discussionmentioning
confidence: 98%